The state and life chances in urban China : redistribution and stratification, 1949-1994 - Zhou, Xueguang, 1959- (Cambridge University Press, 2004)
Using life history information of a national sample of urban residents, this book examines how shifting state policies and political processes led to drastic fluctuations of oppurtunities in education attainment, employment, promotions, and economic benefits over the 45-year history and over individuals' life courses.